Understanding the stability mechanisms of lentil legumin-like protein and polysaccharide foams. (December 2016) - Jarpa-Parra, M.; Tian, Z.; Temelli, Feral; Zeng, Hongbo; Chen, L.
Abstract: Foaming properties of lentil legumin-like protein were investigated in the presence of guar gum, xanthan gum and pectin at different environmental pH conditions (3.0, 5.0, and 7.0). The protein foaming capacity was not significantly impacted by adding polysaccharides, whereas foam stability was greatly enhanced at pH 3.0 and 5.0, leading to formation of long-life foams in most samples with the highest mean life value of 275 min at pH 5.0 in the presence of pectin. Investigation of the stability mechanisms revealed that at pH 3.0, the presence of the coacervates stabilized the foams against collapse due to the formation of an electrostatically cross-linked gel-like interfacial network. At pH 5.0, aggregates were formed that adsorbed to the interface to form stiff and thick interfacial network, avoiding foam coarsening. Aggregates also plugged the junctions of the Plateau borders, slowing down the drainage by a jamming effect, and dramatically increased apparent viscosity of the foams, thus favoring the immobilization of the lamellar water surrounding the gas bubbles. The thermodynamic incompatibility at pH 7.0 resulted in a phase separation of protein and polysaccharide in the interfacial protein membrane. This induced a disruption of the protein layer around the bubbles making it weaker and easier to break, leading to reduced foaming stability. The findings revealed that guar, xanthan, and pectin can improve the stability of lentil legumin-like protein foams at mild acidic pH, creating long-life foams, which would be particularly useful in the food industry where aerated structures must be preserved for a long period of time before solidifying or gelling. Graphical abstract: Highlights: Long-life foams were formed by lentil legumin-polysaccharide complexes. Foam stability was greatly increased at mildly acidic pH by adding polysaccharides. Complex coacervates or aggregates enhanced interfacial networks and foam stability. Interfacial layer disruption due to phase separation at pH 7 reduced foam stability.